Land-use change and sustainability in the south-eastern oases of Morocco - Akdim, Mariam; Akdim, Hamid; Sabiri, Aboubakr; Alami , Anouar (Bulletin of Geography. Socio-economic Series, 2023)
The study apprehends modern versus traditional land-use changes in the Moroccan oases. The traditional local knowledge and land-use that ensured ecological equilibrium for centuries is decreasing. Modern entrepreneuship practices are increasing and have risky environmental impacts. By using the spatial and factor analyses, we confirm the spatial disparities in the region and distinguish four different groups of communes (in high mountain communes, traditional agriculture favors resources’ conservation; downstream communes experience greater changes and ecological ruptures). The recommendations of the study include the need to rethink adopted development models and elaborate new actions that respect local specificities, consider environmental equilibrium and rehabilitate local ecosystems.